2010
DOI: 10.5539/gjhs.v2n1p106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intrinsic Airway Acidification in Pulmonary Tuberculosis

Abstract: Exhaled breath condensate acidification reflects the presence of airway acidification. Mycobacterium tuberculosis is an organism particularly sensitive to acidity. We aimed to determine if there is evidence of airway acidification in a cross section of patients with active tuberculosis.We enrolled 51 subjects with active tuberculosis in Ghana and Thailand, and compared them to control subjects. We collected exhaled breath condensate, and assayed for pH after gas standardization.Exhaled breath condensate pH fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…For this study, EBC was shipped on dry ice at variable time intervals to the University of Virginia for deaeration (at ambient temperature 26 ) and pH measurement by investigators blinded to the identity of characteristics of the subject. Note that deaeration and storage at 2 20°C yields reproducible pH results, even in intercontinental shipping, 20,27,28 across pH range 5-8 (n 5 15); repeat assays give an r 2 5 0.975. 27 Samples were deaerated using argon as previously described for 7 min, and stable pH recorded as previously described.…”
Section: Ebc Collectionmentioning
confidence: 93%
“…For this study, EBC was shipped on dry ice at variable time intervals to the University of Virginia for deaeration (at ambient temperature 26 ) and pH measurement by investigators blinded to the identity of characteristics of the subject. Note that deaeration and storage at 2 20°C yields reproducible pH results, even in intercontinental shipping, 20,27,28 across pH range 5-8 (n 5 15); repeat assays give an r 2 5 0.975. 27 Samples were deaerated using argon as previously described for 7 min, and stable pH recorded as previously described.…”
Section: Ebc Collectionmentioning
confidence: 93%
“…In light of the overall health benefits of tannins, [1] the capacity of these systemst or eleaset heir loaded active materiali na ne nvironment that mimics conditions of certain parts of the human body was targeted. [66] Furthermore, generated Fe-TMCs exhibit more favorable dimensions under these condi-tions ( Figure 9C)a nd are able to load high amounts of active substrate. Despite the variousr esults obtained in the pH stability studies, as olution of pH 7.4 was chosen as the standard conditions for loading and release studies in light of the potential application in pharmaceutical andm edical applications, as pH 7.4 is exemplary forb oth the pH of human blood and of the liquid in human lungs; [64,65] most notablyi nl ight of the specific application discussed below,7 .4 is also close to the pH of the liquid in lungs of tuberculosis patients.…”
Section: Release Studiesmentioning
confidence: 97%
“…It is known that the pH of ELF can become more acidic in certain disease states. For instance, in TB infection, exhaled air is known to be more acidic than in healthy volunteers . The clinical studies used to compare with the simulation results include both healthy individuals and also some individuals with different lung pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in TB infection, exhaled air is known to be more acidic than in healthy volunteers. 44 The clinical studies used to compare with the simulation results include both healthy individuals and also some individuals with different lung pathologies. In most of the studies, the actual pH of the collected lung fluid was not reported and thus decreased ELF pH is one plausible explanation for some of the underprediction of drug concentration seen.…”
Section: Discussionmentioning
confidence: 99%